Studies on thermal and mechanical behavior of nano TiO2 - epoxy polymer composite - Sagar, J. S.; Madhu, G. M.; Koteswararao, Jammula; Dixit, Pradipkumar (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2022)
The present study purposely is to study the properties of TiO2-epoxy composites. TiO2 was synthesized using the peptization and hydrolysis method and the synthesized powder is in anatase form. The present work aimed to develop the low TiO2 filler epoxy composites for the improved thermal and mechanical properties. The synthesized TiO2 was used as a filler along with epoxy composite and the epoxy - TiO2 nanocomposites were fabricated using the low filler concentration of 0.5, 1.0, 1.5, 2.0, and 2.5% by weight. The glass transition temperature (Tg), regardless of the nanoparticles, was almost the same at 71.23oC. Tensile strength was maximum at 0.5%wt.; further increase in filler loading resulted in a linear reduction of tensile strength. Tensile modulus increased linearly and was found to be maximum at 2.5wt%. Meanwhile, compressive strength was maximum at 0.5%, and compressive modulus increased with filler increase. The present work mainly aimed to develop low filler concentrations.